Cell biology and genetics - Starr, Cecie; Taggart, Ralph; Evers, Christine; Starr, Lisa (Brooks/Cole, Cengage Learning, 2013)
Provides real-world applications and helps you think critically about them. This edition offers a new Learning Roadmap in each chapter to help you gain a full understanding. It enables you to go beyond rote memorization and prepare you to make important decisions in life that require an understanding of biology and the process of science.